Ceftobiprole Medocaril Is an Effective Post-Exposure Treatment in the Fischer 344 Rat Model of Pneumonic Tularemia - Mark M. Hahn; Cheryl A. Triplett; Michael S. Anderson; Jennifer I. Smart; Karine Litherland; Stephen Keech; Franziska von Siebenthal; Mark Jones; Andrew J. Phipps; Lisa N. Henning (MDPI AG, 2023)
Francisella tularensis subspecies tularensis is a category-A biothreat agent that can cause lethal tularemia. Ceftobiprole medocaril is being explored as a medical countermeasure for the treatment of pneumonic tularemia. The efficacy of ceftobiprole medocaril against inhalational tularemia was evaluated in the Fischer 344 rat model of infection. The dose was expected to be effective against F. tularensis isolates with ceftobiprole minimum inhibitory concentrations ≤0.5 µg/mL. Animals treated with ceftobiprole medocaril exhibited a 92% survival rate 31 days post-challenge, identical to the survival of levofloxacin-treated rats. By comparison, rats receiving placebo experienced 100% mortality. Terminally collected blood, liver, lung, and spleen samples confirmed disseminated F. tularensis infections in most animals that died prior to completing treatments (placebo animals and a rat treated with ceftobiprole medocaril), although levels of bacteria detected in the placebo samples were significantly elevated compared to the ceftobiprole-medocaril-treated group geometric mean. Furthermore, no evidence of infection was detected in any rat that completed ceftobiprole medocaril or levofloxacin treatment and survived to the end of the post-treatment observation period. Overall, survival rates, body weights, and bacterial burdens consistently demonstrated that treatment with ceftobiprole medocaril is efficacious against otherwise fatal cases of pneumonic tularemia in the rat model.